PENGEMBANGAN DASHBOARD KONTROL PENGENDALIAN MUTU PADA BAGIAN PRINTING DAN EMBOSS PT. MEGAH MAS PRIMA - Arief Herdiansah; Rosdiana Rosdiana; Febriana Wulandani (Jurnal Ilmiah Matrik, 2019)
Abstract : Quality control of production is an important thing that must be done by manufacturing companies to be able to produce products in accordance with customer orders. Quality Control (QC) is the department that is responsible for maintaining the quality of the products produced in accordance with predetermined standards. This research was conducted at PT Megah Mas Prima, currently the company still uses conventional methods in the process of creating reports on the results of printing and embossed production. The process of entering the recapitulation data of QC results using Microsoft Excel application, this is very difficult for QC staff because there are many criteria and material codes that must be entered so that the process of making reports requires quite a long time and the level of human error is also high. This research has produced an information system that can assist quality control staff in entering QC data, create QC reporting and accelerate the process of delivering data to QC managers and to other parties who need it.